THE VECTOR OF ECONOMIC REFORMS AS A FACTOR IN IMPROVING THE QUALITY OF LIFE OF THE POPULATION IN THE REPUBLIC OF UZBEKISTAN - Abdullaev Anvarjon Farxadovich (Ecomind Press, 2025)
In the article it is investigated the bases of the theory of growth in the conditions of a postmodern which have arisen a contradiction, factors and their influences on economic growth. Among problems of scientific and practical character which solution is based on the theory of macroeconomic growth the greatest interest is attracted identification of effectively operating sources and types of economic growth. The social groups interested in economic growth and their number are considered, it is presented the concept of sustainable development and a problem of national economic growth are presented.
Keywords: Economic growth, economic development, types of economic growth, factors, concept of sustainable development, demographic processes, socio-economic factors, features, demographic dividend, population migration.